QSCILLOSCOPE: A PC-Based Real Time Oscilloscope - Yiqi, Tew; Bok-Min, Goi (2008)
The scenery of this paper is to design a PC-based Real Time Oscilloscope, called "Qscilloscope". Qscilloscope is capable to connect a computer with a small device via universal serial bus (USB) port for voltage signal waveform display and alteration. It detects maximum +20V to minimum -20V with the input frequency range from 0.1Hz - 1 kHz. Furthermore, it interfaces with host PC via the USB port from 9.6k to 115.2k baud rate.